Pengabdian Kepada Masyarakat Melalui Kuliah Kerja Nyata Tematik (KKN-T) Di Desa Randobawailir Kabupaten Mandirancan - Timur, Bintang; Layalia, Nudya; Dwy Hermawan, E; Dhevyanto, Benny (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
Thematic Community Service (KKN-T) is an integral part of the Tridharma of Higher Education, which requires students to play an active role in community empowerment through education, research, and community service. Through a qualitative approach with direct participant observation methods to the village community to gain a deep understanding of the social phenomena that occur in Randobawailir Village, this article discusses the implementation of KKK-T group 49 of Gunung Jati Swadaya University, which took place in Randobawailir Village, Mandirancan District, Kuningan Regency, which has four work programs engaged in: empowerment of village MSMEs, education, environment and health. through the research method of participant observation of the Randobawailir village community to find out about daily life in the village. KKN-T activities in the village include empowerment of MSMEs, socialization of anti-bullying and healthy living behaviors, construction of garden houses and toddler immunizations, stunting nutrition seminars and classes for pregnant women that can be implemented smoothly. This KKN-T research in Randobawailir Village is expected to provide useful knowledge for the University, Students and the Village Community and become a foundation for future research.